Children's cancer pain in a world of the opioid epidemic: Challenges and opportunities. Issue 4 (18th December 2019) - Fortier, Michelle A.; Yang, Sun; Phan, Michael T.; Tomaszewski, Daniel M.; Jenkins, Brooke N.; Kain, Zeev N.
Abstract: The opioid crisis in the United States has grown at an alarming rate. Children with cancer are at high risk for pain, and opioids are a first‐line treatment in this population. Accordingly, there is an urgent need to optimize pain management in children with cancer without contributing to the opioid crisis. This report details opportunities for this optimization, including clinical practice guidelines, comprehensive approaches to pain management, mobile health, and telemedicine. It is vital to balance appropriate use of analgesics with efforts to prevent misuse in order to reduce unnecessary suffering and minimize unintended harms.